The Netter presenter human anatomy collection - Hansen, John T.; Netter, Frank H. (Frank Henry), 1906-; Icon Learning Systems (Teterboro, NJ : Icon Learning Systems, 2001)
(Producer) Helps one customize, export, and print high-quality medical art from a home computer. A four-way search capability allows searching by region, keyword, system, or plate number.
Title from disc label.
'Featuring images from the complete Atlas of human anatomy, 2nd ed.'
System requirements: IBM-compatible PC (Pentium processor running at 300 MHz or faster recommended); minimum of 32 MB of RAM for Windows 95 and a minimum of 128 MB for Windows 2000 is highly recommended; Windows 95, 98, NT4, ME, and 2000 are supported; monitor of at least 1024 x 768 pixel resolution displaying 16 bit color depth or more.
System requirements: Macintosh, PowerPC Macintosh or compatible computer, the programs runs best on a PowerPC G3 processor running at 266 MHz or faster; miminum RAM and processor speed requirements depend on the MacOS version installed, with a minimum of 32 MB of RAM for MacOS8.1 and a minimum of 64 MB for MacOS 9; MacOS 8.1 or later is supported, the program runs in MacOS X in the'Classic' environment; monitor of at least 1024 x 768 pixel resolution and displaying'thousands' of color or more.
Keywords: Anatomy -- Atlases